The Impact of a Food for Education Program on Schooling in Cambodia. Issue 1 (12th February 2014) - Cheung, Maria; Berlin, Maria Perrotta
Abstract: This study is an evaluation of the impact of a food for education program implemented in primary schools (grades 1–6) in six Cambodian provinces between 1999 and 2003. We find that school enrolment increased to varying degrees in relation to different designs of the intervention. We also investigate the effect of the program in terms of completed education and probability of having ever been in school, following up the affected cohorts in a 2009 survey. With an estimated cost of US$85 per additional child in school per year, the program can be considered very cost‐effective within a comparable class of interventions.